2013
DOI: 10.1111/are.12190
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of un-ionized ammonia in live feed cultures of the calanoid copepodAcartia tonsaDana

Abstract: Optimal water quality is considered as being a restriction for marine copepod cultures for live feed. There is a lack of knowledge on the water‐quality conditions in copepod cultures and the effect on copepods. Few studies have investigated the effect of ammonia on copepods, and fewer reports No Observed Effect Concentrations (NOEC) and Lowest Observed Effect Concentrations (LOEC), which provides safety levels before cultures are affected. This study investigates the tolerance of Acartia tonsa nauplii and adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 40 publications
(58 reference statements)
1
13
0
Order By: Relevance
“…Similar values can be reached also in artificial conditions when a large number of individuals is needed for experimental trials [12], for aquaculture purposes [13][14][15] or when recording the motion of copepods [16]. As a drawback, high densities may impair copepod fitness, reducing food availability and egg production while increasing mortality [17][18][19], boosting the concentration of metabolic products and reducing water quality [20], and decreasing the respiration rate [15]. In addition, increasing copepod abundance can favour the transfer of oil droplets to lower trophic level by direct manipulation and egestion [21].…”
Section: Introductionmentioning
confidence: 69%
“…Similar values can be reached also in artificial conditions when a large number of individuals is needed for experimental trials [12], for aquaculture purposes [13][14][15] or when recording the motion of copepods [16]. As a drawback, high densities may impair copepod fitness, reducing food availability and egg production while increasing mortality [17][18][19], boosting the concentration of metabolic products and reducing water quality [20], and decreasing the respiration rate [15]. In addition, increasing copepod abundance can favour the transfer of oil droplets to lower trophic level by direct manipulation and egestion [21].…”
Section: Introductionmentioning
confidence: 69%
“…On the other hand, Støttrup et al (1986) reported that the daily copepod mortality rate of A. tonsa was constant at 5% in the optimal salinity gradient, but it increased by about 50% or more in high salinity with values above 25 psu (Medina and Barata, 2004). It is not practical to accommodate more than 50% mortality of live prey in mass production (Jepsen et al, 2015). The mortality of A. ohtsukai observed for 10 days showed a low rate of less than 25% on average at all water temperatures and salinities except at salinity values of 10 and 15 psu at a water temperature of 10 • C. Further, extensive salinity changes, except for a high salinity value of 33 psu, did not significantly affect HS in A. ohtsukai over 48 h. However, in the low temperature (10 and 15 • C) experiment, no eggs were produced at salinities of 10, 15, and 33 psu.…”
Section: Discussionmentioning
confidence: 99%
“…1b and c, where the viability of eggs is constant for samples with much higher egg abundances than in the long term experiment. In dense static A. tonsa cultures, the level of ammonia can reach toxic limits due to the pH dependent equilibrium between NH 4 /NH 3 [43]. The release of NH 4 /NH 3 from A. tonsa eggs is unknown, but expected to be negligible.…”
Section: Discussionmentioning
confidence: 99%
“…The culture was started at the Danish Institute for Fisheries and Marine Research and has been continuously maintained for > 35 years without being restocked with wild animals. The physiology and ecology of the culture has been described in several publications [15, 16, 20, 29, 30, 41, 43].…”
Section: Methodsmentioning
confidence: 99%